Analisis Faktor-Faktor Penyebab Terjadinya Kecelakaan Kerja di Tambang Batubara - Ella Asri Fauziah; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
One industrial sector that is very beneficial for Indonesia is mining. Its contribution includes export revenues, regional development, increased economic activity, job creation, and sources of funding for both national and regional budgets. The coal mining industry has a significant risk of work accidents and a high level of danger. The risk of work accidents in coal mining is very high, as evidenced by work accidents being one of the main causes of death in this industry. Finding the causes of work accidents in coal mining is the aim of this literature review. Research findings show that ignorance, lack of experience in using personal protective equipment (PPE), worker errors (unsafe actions), and failure to build a work safety culture in an organization are the main factors causing work accidents in the coal mining industry.